DINAMIKA FORMULASI AKAD TERHADAP PENGELOLAAN DANA HAJI DI INDONESIA - Maizul Imran; Rio Satria (Alhurriyah, 2018)
The development of a hajj fund that is so great has the potential to be used in supporting the implementation of a better quality Hajj through effective, efficient, transparent, accountable, and in accordance with the provisions of legislation. The strategy that has been taken by the Ministry of Religion to optimize the management of the Hajj fund so that its benefits can be used to improve the quality of Hajj implementation is by developing these funds through investment. But in fact, the dynamics that occur are in the BPIH deposit. When the funds are managed which constitute funds deposited by prospective pilgrims to the government (Ministry of Religion or BPKH) to finance the implementation of their pilgrimage, problems arise regarding the appropriate contract formulation to be used, whether wakalah contract, mudlarabah (profit sharing), or altogether no longer need a contract, because the government acts as a statutory power for prospective pilgrims, as consideration of the decision of the Constitutional Court (MK).